Bone Marrow Findings Secondary to Antineoplastic Compounds: Hematopoietic, Bone, and Cytokine Cross Talk. (October 2017) - Loberg, Lise I.; Logan, Michael; Barnhart, Kirstin; Fossey, Stacey; Whitney, Katharine
New medullary bone formation has been observed in rats administered a variety of antineoplastic compounds. Similar effects reported in rats administered granulocyte colony-stimulating factor (G-CSF) were attributed to exaggerated pharmacology of G-CSF as a cytokine and growth factor, resulting in stromal proliferation in addition to the intended hematopoietic effects. Similar phenomena of marrow stromal change are reported among other species in association with various growth factors. Case study summaries of test item–related histopathologic changes in bone marrow, reflecting trabecular and/or endosteal new bone formation, are presented. In each of these cases, it was concluded that the new medullary bone and stromal proliferation did not reflect a primary target–related toxicity; rather, the mesenchymal changes were attributed to nonspecific, secondary effects of cytokines elaborated in response to primary cytotoxic effects on hematopoietic cells with subsequent impact on circulating blood cells. The common features associated with marrow stromal changes in the case studies, as well as with a variety of pharmacologic compounds across several species described in the literature, are hematologic effects and/or changes in growth factor levels and cytokine expression.